An Analysis of Annual Reports From the Sustainable Development Goals Perspective - Hacihasanoglu, Erk; Unlusoy, Oemer Faruk; Madenoglu, Fatma Selen (Emerald Group Publishing Ltd, 2023)
PurposeThe sustainable development goals (SDGs) are introduced to guide achieving the sustainable goals and tackle the global problems. United Nations members may perform activities to achieve the predetermined goals and report on their SDG activities. The comprehension and commitment of several stakeholders are essential for the effective implementation of the SDGs. Countries encourage their stakeholders to perform and report their activities to meet the SDGs. The purpose of this study is to investigate the extent to which corporations' annual reports address the SDGs to assess and comprehend their level of commitment to, priority of and integration of SDGs within their reporting structure. This research makes it easier to evaluate corporations' sustainability performance and contributions to global sustainability goals by looking at the extent to which they address the SDGs.Design/methodology/approachIn the study, it is revealed to what extent the reports meet the SDGs with the multilabel text classification approach. The SDG classification is carried out by examining the report with the help of a text analysis tool based on an enhanced version of gradient boosting. The implementation of a machine learning-based model allowed it to determine which SDGs are associated with the company's operations without the requirement for the report's authors to perform so. Therefore, instead of reading the texts to seek for "SDG" evidence as typically occurs in the literature, SDG proof was searched in relevant texts.FindingsTo show the feasibility of the study, the annual reports of the leading companies in Turkey are examined, and the results are interpreted. The study produced results including insights into the sustainable practices of businesses, priority SDG selection, benchmarking and business comparison, gaps and improvement opportunities identification and representation of the SDGs' importance.Originality/valueThe findings of the analysis of annual reports indicate which SDGs they are concerned about. A gap in the literature can be noticed in the analysis of annual reports of companies that fall under a particular framework. In addition, it has sparked the idea of conducting research on a global scale and in a time series. With the aid of this research, decision-making procedures can be guided, and advancements toward the SDGs can be achieved.
Keywords: Multilabel Text Classification; Extreme Gradient Boosting; Annual Report; SDGs